2010
DOI: 10.1016/j.archoralbio.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric analysis and immunolocalization of RANKL and OPG during the alveolar healing process in female ovariectomized rats treated with oestrogen or raloxifene

Abstract: Ovariectomy delays the alveolar healing process and interferes with bone turnover through the balance between RANKL and OPG. Oestrogen replacement or raloxifene treatment did not totally recover the oestrogen-deficient state. However raloxifene treatment showed more satisfactory results than oestrogen replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
40
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 42 publications
10
40
0
1
Order By: Relevance
“…A previous study 36 reported intense and moderate RANKL staining on osteoblasts and osteoclasts. Positive BSP staining was also previously reported 12 during the first week after ovariectomy and OCC expression was clearly changed by ovariectomy 37 .…”
Section: Discussionsupporting
confidence: 79%
“…A previous study 36 reported intense and moderate RANKL staining on osteoblasts and osteoclasts. Positive BSP staining was also previously reported 12 during the first week after ovariectomy and OCC expression was clearly changed by ovariectomy 37 .…”
Section: Discussionsupporting
confidence: 79%
“…These foregoing findings was in agreement with other studies (39) , which found that the alveolar repair process associated with the receptor activator of NF-κB ligand and OPG pattern being inversely proportional. As there was an increase in bone formation during the course of the analyzed periods, while there was a reduction in the expression of these proteins, indicating complete filling of the alveolar process associated with a balance in bone turnover.…”
Section: Discussionsupporting
confidence: 93%
“…Comparatively, Luvizuto et al 26 studied RANK-L and OPG during the alveolar healing process in female ovariectomized rats treated with estrogen or raloxifene. They found that both studied proteins were immunodetected in osteoblasts, osteocytes and/or in bone lining cells, which are the predominant cells at the studied stages of alveolar bone healing at 7, 14, 21, 28 and 42 days.…”
mentioning
confidence: 99%